Anemia, diet and therapeutic iron among children living with HIV: a prospective cohort study - Shet, Anita (BMC Pediatr, 2015)
BACKGROUND: Children living with HIV have higher-than-normal prevalence of anemia. The beneficial effect of therapeutic iron has been questioned in the setting of high prevalence of infections. This study examines anemia prevalence and effect of standard therapeutic iron on HIV disease progression among children. METHODS: Perinatally-infected children aged 2–12 years were enrolled at three sites in southern India, and were followed for 1 year with clinical assessments, dietary recall and anthropometry. Laboratory parameters included iron markers (ferritin, soluble transferrin receptor) and other micronutrient levels (vitamin A, B(12), folate). Iron was given to anemic children based on WHO guidelines. Statistical analyses including frequency distributions, chi square tests and multivariate logistic regression were performed using Stata v13.0. RESULTS: Among 240 children enrolled (mean age 7.7 years, 54.6 % males), median CD4 was 25 %, 19.2 % had advanced disease, 45.5 % had malnutrition, and 43.3 % were on antiretroviral treatment (ART) at baseline. Anemia was prevalent in 47.1 % (113/240) children. Iron deficiency was present in 65.5 %; vitamin A and vitamin B(12) deficiency in 26.6 % and 8.0 % respectively; and anemia of inflammation in 58.4 %. Independent risk factors for anemia were stunting, CD4 < 25 %, detectable viral load ≥400 copies/ml and vitamin A deficiency. Inadequate dietary iron was prominent; 77.9 % obtained less than two-thirds of recommended daily iron. Among clinically anemic children who took iron, overall adherence to iron therapy was good, and only minor self-limiting adverse events were reported. Median hemoglobin rose from 10.4 g/dl to 10.9 mg/dl among those who took iron for 3 months, and peaked at 11.3 mg/dl with iron taken for up to 6 months. Iron was also associated with a greater fall in clinical severity of HIV stage; however when adjusted for use of ART, was not associated with improvement in growth, inflammatory and CD4 parameters. CONCLUSIONS: Children living with HIV in India have a high prevalence of anemia mediated by iron deficiency, vitamin A deficiency and chronic inflammation. The use of therapeutic iron for durations up to 6 months appears to be safe in this setting, and is associated with beneficial effects on anemia, iron deficiency and HIV disease progression.